Is the presence of varicocele associated with static and dynamic components of benign prostatic hyperplasia/lower urinary tract symptoms in elderly men?. (23rd July 2014) - Otunctemur, Alper; Ozbek, Emin; Besiroglu, Huseyin; Dursun, Murat; Sahin, Suleyman; Koklu, Ismail; Erkoc, Mustafa; Danis, Eyyup; Bozkurt, Muammer; Gurbuz, Ahmet
<x xml:space="preserve">Abstract</x> Objectives To evaluate the relationship between varicocele and benign prostatic hyperplasia/lower urinary tract symptoms in patients over the age of 40 years. Methods A total of 1040 patients with benign prostatic hyperplasia/lower urinary tract symptoms were evaluated for prostate volume, testicular volume, testicular consistency, total testosterone, total prostate‐specific antigen and body mass index. A questionnaire including International Prostate Symptom Score and a uroflow test were also carried out. The presence and grade of varicocele was determined in each patient by physical examination. Results Varicocele was found bilaterally in 22.3% and unilaterally in 25.7% of the patients. There was no difference in terms of age and body mass index distribution between subgroups. When grouping patients for varicocele laterality, total testosterone (P = 0.04), prostate volume (P = 0.009) and total prostate‐specific antigen (P = 0.02) level were significantly different. Similarly, these parameters were significant between patients with grade 1, 2 and 3 varicocele. Total testosterone level (P = 0.02) and prostate volume (P = 0.035) were found to be significantly different when patients were grouped according to testicular size. A positive correlation was found between testosterone level and prostate volume (P = 0.004; r2 = 0.084). Conclusions Bilateral and/or higher‐grade varicocele is associated with lower prostate volume and testosterone levels, as well as lower prostate‐specific antigen levels. However, it is not associated with dynamic components of benign prostatic hyperplasia/lower urinary tract symptoms in patients over the age of 40 years.